Cross-sectional analysis of Piroplasma species-infecting camel (Camelus dromedaries) in Egypt using a multipronged molecular diagnostic approach - Mahdy, Olfat A.; Nassar, Ahmed M.; Elsawy, Bassma S. M.; Alzan, Heba F.; Kandil, Omnia M.; Mahmoud, Mona S.; Suarez, Carlos E. (Frontiers in Veterinary Science, 2023)
Camel piroplasmosis is a tick-borne disease (TBD) caused by hemoprotozoan parasites. Hereby, we describe a cross-sectional study aiming at identifying Piroplasma spp.-infecting camels in Egypt using a multipronged molecular diagnostic approach. A total of 531 blood samples from camels (Camelus dromedarius) were collected from slaughterhouses at different governorates in Egypt for analysis during the period from June 2018 to May 2019. Piroplasma spp. was identified using microscopical examination and several different and sequential polymerase chain reaction (PCR) assays targeting the 18S rRNA genes. The overall prevalence of Piroplasma spp. in microscopical and molecular analyses in the samples was 11% (58/531) and 38% (203/531), respectively. Further discriminative multiplex PCR analysis targeting the 18S rRNA gene applied on all Piroplasma spp.-positive samples allowed the detection of Theileria equi (41%), Babesia caballi (5.4%), Babesia bigemina (0.5%), and Babesia bovis (4%). Additionally, the blast analysis of nested (n) PCR, targeting the V4 region, amplicon sequences resulted in the identification of B. vulpes (22%), Babesia sp. (9%), and Theileria sp. (3%). Overall, the results of this study confirmed the high prevalence of TBDs caused by several types of piroplasm hemoparasites in camel and suggests the need for future interventions aimed at improving the control of these potentially debilitating diseases that may be t-hreatening important economic resources and food security in Egypt.